Research cards as a strategy for the formation of investigative competences - Loayza Maturrano, Edward Faustino (2021)
The objective of the study is to know the relationship between the training strategy of research recruitment and the development of research competences in university students. The research is quantitative, non-experimental, with a correlational design, and it tries to analyze and evaluate the relationship between the variables: strategy of research registration and research competencies. The type of sampling was by convenience and was represented by 58 university students. The instrument for self-assessment of investigative competencies developed and validated by Carla Paz et al. (2017) was used. The data analysis was performed using the SPSS version 26 software package, which reached the frequencies and the description of the percentage values. The results show that there is a high correlation in the competences: information search, ability to develop the research methodology and ability to communicate the results; and there is a moderate correlation in competencies: ability to use technological resources for research and ability to work as a team for research. The conclusions confirm the positive correlation between the training strategy of research recruitment and the development of research competencies in university students. Keywords: Research skills; student research; science education; teaching strategies; college students.